17-alpha-hydroxyprogesterone Caproate for Maintenance Tocolysis: A Systematic Review and Metaanalysis of Randomized Trials. Issue 2 (June 2016) - Saccone, G.; Suhag, A.; Berghella, V.
Abstract : ( Am J Obstet Gynecol. 2015;213(1):16–22) Preterm birth is the leading cause of neonatal death and morbidity in the United States. Preterm labor can be halted using tocolytic agents, but since a mother's risk of preterm birth remains high even once preterm labor has been arrested, some suggest the use of continued maintenance tocolysis.